Exergy analysis of supercritical cycle for 1000 MW power generation using without reheat, single and double reheat / I. Satyanarayana, A.V.S.S. Kumara Swami Gupta and Govinda Rajulu Kosireddy - Satyanarayana, I.; Gupta, A.V.S.S. Kumara Swami; Kosireddy, Govinda Rajulu (UiTM Press, 2010)
This paper presents Exergy analysis of Supercritical Rankine cycle without reheat, single reheat and double reheat for higher power generation of modern steam power plants for 1000 MW. A computer code has been developed to estimate the steam properties using ISI steam tables. The temperature and pressure inlet to the turbine and exhaust pressure from the turbine are identified as key parameters in this analysis. Cycle efficiency, exergy efficiency, work ratio, steam rate and heat rate has been studied. Total exergy loss and fractional exergy loss of all the components in the cycle have been analyzed. Effect of decreasing the discharge pressure in the condenser, effect of flue gas inlet and outlet temperature of the boiler and Effect of reheat pressure and number of reheats in the boiler has been studied. It is observed that both efficiencies increases more with temperature rise than pressure rise. The effects of these parameters on the exergy loss of each component have also been studied.